Digital Journalism and Press Freedom: The Relevance of the Press Law in the Era of Social Media Platforms - Tenang Haryanto; Syarafina Dyah Amalia; Manunggal Kusuma Wardaya (Rechtenstudent, 2025)
Advances in digital technology have significantly changed the face of journalism and press freedom. Today, people can easily create and disseminate information through digital platforms, such as social media, without the need to be part of the official media. This phenomenon raises legal issues, especially with regard to the relevance of Law No. 40/1999 on the Press in the context of digital journalism. This research applies the normative juridical method with a regulative and conceptual approach to analyse the compatibility of the norms in the Press Law with the practice of journalism in the digital era. The research findings show that many current journalistic activities  including the creation and dissemination of news by non-press persons or institutions are not expressly regulated in the Press Law. As a result, supervision is less effective, the risk of spreading misinformation and disinformation increases, and legal protection for digital journalism actors is blurred. The current Press Law only covers a small part of modern journalism practices and is not responsive to the challenges of press freedom in the decentralised digital space. Therefore, it is necessary to update regulations or develop supporting norms that can deal with the realities of today's digital media without compromising the principle of press freedom.